Evaluation of National Oral Cancer Control Policies and Their Impact on Early Detection and Survival Outcomes of Patients with Oral Squamous Cell Carcinoma - Dr Aleena Shaheryar Sadiq, Dr Aiza Sohail Khan, Dr Usman Manzoor Warraich, Dr. Umar Farooq Khan, Dr Shahida Maqbool, Dr Mohid Abrar Lone, Dr Nabeel Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Oral squamous cell carcinoma (OSCC) has an alarmingly high incidence rate in Pakistan, furtherworsened by the fact that most patients do not survive long enough after diagnosis whichunderscores the vital need for timely intervention. Although the main aim of the National Oral Cancer Control Policies (NOCCPs)